Antenatal Weight Management: Women's Experiences, Behaviours, and Expectations of Weighing in Early Pregnancy. (24th October 2016) - Swift, J. A.; Pearce, J.; Jethwa, P. H.; Taylor, M. A.; Avery, A.; Ellis, S.; Langley-Evans, S. C.; McMullen, S.
Abstract : The current emphasis on obstetric risk management helps to frame gestational weight gain as problematic and encourages intervention by healthcare professionals. However pregnant women have reported confusion, distrust, and negative effects associated with antenatal weight management interactions. The MAGIC study (MAnaging weiGht In pregnanCy) sought to examine women's self-reported experiences of usual-care antenatal weight management in early pregnancy and consider these alongside weight monitoring behaviours and future expectations. 193 women (18 yrs+) were recruited from routine antenatal clinics at the Nottingham University Hospital NHS Trust. Self-reported gestation was 10–27 weeks, with 41.5% (n = 80 ) between 12 and 14 and 43.0% (n = 83 ) between 20 and 22 weeks. At recruitment 50.3% of participants (n = 97 ) could be classified as overweight or obese. 69.4% of highest weight women (≥30 kg/m 2 ) did not report receiving advice about weight, although they were significantly more likely compared to women with BMI < 30 kg/m 2 . The majority of women (regardless of BMI) did not express any barriers to being weighed and 40.8% reported weighing themselves at home. Women across the BMI categories expressed a desire for more engagement from healthcare professionals on the issue of bodyweight. Women are clearly not being served appropriately in the current situation which simultaneously problematizes and fails to offer constructive dialogue.